2021
DOI: 10.1259/bjr.20210570
|View full text |Cite
|
Sign up to set email alerts
|

Multisystem inflammatory syndrome in children associated with SARS-CoV-2: extracardiac radiological findings

Abstract: Objective: Multisystem inflammatory syndrome in children (MIS-C) is seen as a serious delayed complication of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. The aim of this study was to describe the most common imaging features of MIS-C associated with SARS-CoV-2. Methods: A retrospective review was made of the medical records and radiological imaging studies of 47 children (26 male, 21 female) in the age range of 25 months–15 years who were diagnosed with MIS-C between August 2020 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…11 Additional case reports and series demonstrated similar findings. 1222 Our case and review of other reported cases strengthens the evidence of association between retropharyngeal inflammation and MIS-C. Absence of an association of retropharyngeal inflammation and MIS-C in the literature might have led to a relatively late diagnosis in some patients such as occurred with our patient.…”
Section: Discussionsupporting
confidence: 81%
“…11 Additional case reports and series demonstrated similar findings. 1222 Our case and review of other reported cases strengthens the evidence of association between retropharyngeal inflammation and MIS-C. Absence of an association of retropharyngeal inflammation and MIS-C in the literature might have led to a relatively late diagnosis in some patients such as occurred with our patient.…”
Section: Discussionsupporting
confidence: 81%
“…A systemic review by Ucan et al including 47 patients MIS-C concluded that peribronchial cuffing, perihilar or diffuse infiltration, consolidation, atelectasis, cardiomegaly, and pleural effusion were the most common imaging findings on chest radiography. 15 Three main thoracic imaging findings were observed in pediatric patients with MIS-C in another review including 20 patients: heart failure, acute respiratory distress syndrome pattern, and pulmonary embolus. 16 In our study, eight patients were found to have pulmonary parenchymal infiltration on chest X-ray imaging, and pleural effusion was observed in seven patients.…”
Section: Discussionmentioning
confidence: 99%
“… 25 In PIMS, respiratory involvement is relatively rare or mild (mainly bronchial thickening), whereas extra‐respiratory radiological involvement is more common with cardiomegaly, mesenteric inflammation, hepatosplenomegaly, periportal edema, ascites, or thickening of the digestive walls. 30 , 53 …”
Section: Radiological Signs Of Covid‐19 In Childrenmentioning
confidence: 99%
“…It is also important to note that pulmonary embolism must be considered in adolescents, especially in cases of thromboembolic risk factors or suggestive biological markers 25 . In PIMS, respiratory involvement is relatively rare or mild (mainly bronchial thickening), whereas extra‐respiratory radiological involvement is more common with cardiomegaly, mesenteric inflammation, hepatosplenomegaly, periportal edema, ascites, or thickening of the digestive walls 30,53 …”
Section: Radiological Signs Of Covid‐19 In Childrenmentioning
confidence: 99%